Antimicrobial Efficacy of Garlic on Food Borne Pathogens in Broiler Meat - S., Sudharshan.; M.N., Fairoze.; R, Prabha.; C, Renuka Prasad.; D, Rathnamma. (Journal of Meat Science, 2011)
Spices have been proven traditionally to be used for food preservation. The present study was conducted to evaluate the efficiency of aqueous extract and essential oil of garlic as decontaminating agents in chicken carcasses. The antimicrobial effect of garlic on Salmonella typhimurium, E. coli and Staphylococcus aureus was evaluated by challenging the broiler carcasses with specific cultures of test organisms and marinating them with different levels of garlic extract there after. Microbial analysis was carried out after 0, 3, 6, 12, 24 and 48 hours of refrigerated storage (8± 2 0C). Dipping with aqueous extract of garlic (100%) was found to be more efficient in reducing bacterial pathogens among various treatments. Greater reduction in Total Viable Count (TVC), Salmonella typhimurium, E. coli and Staphylococcus aureus count was observed in spiked chicken legs inoculated with test organisms and marinated with 2.5 per cent garlic extract.